Analysis of Joint Property Distribution Using The Concept Of Jurimetry: Perspectives From John Rawls And Jeremy Betham's Theories Of Justice - Alia Azizah; Mohammad Yasir Fauzi; Gandhi Liyorba Indra (LEGAL BRIEF, 2025)
The division of joint property as regulated in Article 97 of the Compilation of Islamic Law (KHI) is set at half (1/2), unless otherwise specified in the marriage agreement. This approach is often used as a reference by judges because it provides legal certainty. However, this provision is often considered to not take into account the condition of wives who bear a double burden, namely taking care of domestic affairs while also playing a role in the public sphere. This study aims to examine the division of joint property using the concept of jurimetry in the perspective of the theory of justice proposed by John Rawls and Jeremy Bentham, in order to evaluate the extent to which substantive justice is reflected through the application of jurimetry in joint property cases. The method used is normative legal research with a legislative, conceptual, and case study approach. The findings of the study indicate that the use of jurimetrics in joint property cases must be combined with the principles of justice according to Rawls and Bentham, so that the division is not solely based on a formal legal approach but also considers aspects of social and moral justice